Credit risk in general equilibrium - Eichberger, Jürgen; Rheinberger, Klaus; Summer, Martin (Working paper, 2011)
Credit risk models used in quantitative risk management treat credit risk analysis conceptually like a single person decision problem. From this perspective an exogenous source of risk drives the fundamental parameters of credit risk: probability of default, exposure at default and the recovery rate. In reality these parameters are the result of the interaction of many market participants: They are endogenous. The authors develop a general equilibrium model with endogenous credit risk that can be viewed as an extension of the capital asset pricing model. They analyze equilibrium prices of securities as well as equilibrium allocations in the presence of credit risk. The authors use the model to discuss the conceptual underpinnings of the approach to risk weight calibration for credit risk taken by the Basel Committee.
Literaturverz. S. 26 - 27
Keywords: Arbeitspapier; Graue Literatur; Kreditrisiko; Regulierung; Bank